A further study on edge-distance-balanced property of the generalized Petersen graphs GP(6n+8, 3). Issue 7 (3rd October 2021) - Ezadi, Mahboubeh
Abstract: A graph G is said to be edge-distance-balanced if for any edge uν of G, the number of edges closer to u than to ν is equal to the number of edges closer to ν than to u . Let GP ( n, k ) be a generalized Petersen graph. It is proven that for any integers n ≥2, the generalized Petersen graph GP (6 n +8, 3) is not edge-distance-balanced.